Age and gender differences in the social patterning of cardiovascular risk factors in Switzerland: the CoLaus study. - Silvia Stringhini (Public Library of Science (PLoS), 2012)
Objectives We examined the social distribution of a comprehensive range of cardiovascular risk factors (CVRF) in a Swiss population and assessed whether socioeconomic differences varied by age and gender. Methods Participants were 2960 men and 3343 women aged 35-75 years from a population-based survey conducted in Lausanne, Switzerland (CoLaus study). Educational level was the indicator of socioeconomic status used in this study. Analyses were stratified by gender and age group (35-54 years; 55-75 years). Results There were large educational differences in the prevalence of CVRF such as current smoking (Δ = absolute difference in prevalence between highest and lowest educational group:15.1%/12.6% in men/women aged 35-54 years), physical inactivity (Δ = 25.3%/22.7% in men/women aged 35-54 years), overweight and obesity (Δ = 14.6%/14.8% in men/women aged 55-75 years for obesity), hypertension (Δ = 16.7%/11.4% in men/women aged 55-75 years), dyslipidemia (Δ = 2.8%/6.2% in men/women aged 35-54 years for high LDL-cholesterol) and diabetes (Δ = 6.0%/2.6% in men/women aged 55-75 years). Educational inequalities in the distribution of CVRF were larger in women than in men for alcohol consumption, obesity, hypertension and dyslipidemia (p<0.05). Relative educational inequalities in CVRF tended to be greater among the younger (35-54 years) than among the older age group (55-75 years), particularly for behavioral CVRF and abdominal obesity among men and for physiological CVRF among women (p<0.05). Conclusion Large absolute differences in the prevalence of CVRF according to education categories were observed in this Swiss population. The socioeconomic gradient in CVRF tended to be larger in women and in younger persons.